Erratum: HER2/p53 ratios among canine mammary tumours and respective derived cell culture (Multidisciplinary Science Journal DOI: 10.29327/multiscience.2022001) - Panegossi, Letícia Colin [UNESP]; Cardoso, Tereza Cristina [UNESP] (Malque Publishing, 2022)
In the Results section (page 3), Figure 1C has been updated (Figure Presented).